ZrO2 / HEDP composite material wrapped with lecithin and preparation method of ZrO2 / HEDP composite material

By effectively combining ZrO2 and HEDP under the wrapping of lecithin, the problem of material binding with very different properties is solved, and the preparation of versatile composite materials is realized, with wide application prospects.

CN119912838APending Publication Date: 2025-05-02CHONGQING JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510085664.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

How to effectively combine ZrO2 and HEDP materials with different properties to form a stable composite system to meet the needs of versatility.

Method used

Ultrasonic dispersion was performed by adding ZrO2 to anhydrous ethanol solution containing HEDP to obtain a uniform first mixed solution, and then dried to obtain an intermediate, and the intermediate was then mixed with a lecithin-containing ethyl acetate solution, and finally the solvent was removed by evaporation under reduced pressure to obtain a lecithin-encapsulated ZrO2/HEDP composite material.

Benefits of technology

It realizes the effective combination of ZrO2 and HEDP, and forms a sustained release system with scale-resistance function, providing new material choices for the preparation of anti-corrosion and anti-scaling coatings, and has a wide range of uses and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912838A_ABST
    Figure CN119912838A_ABST
Patent Text Reader

Abstract

The invention relates to a lecithin-coated ZrO2 / HEDP composite material and a preparation method thereof, and relates to the technical field of materials.The preparation method comprises the following steps that ZrO2 is added into an absolute ethyl alcohol solution containing 1-hydroxyethylidene-1, 1-diphosphonic acid, then ultrasonic dispersion is conducted, and a first mixed solution is obtained; drying the first mixed solution, and obtaining an intermediate after the solution is completely volatilized; adding the intermediate into an ethyl acetate solution containing lecithin to obtain a second mixed solution; the second mixed solution is subjected to reduced pressure evaporation, and after the solvent is completely volatilized, the ZrO2 / HEDP composite material wrapped with lecithin is obtained. According to the invention, ZrO2 with excellent mechanical properties and corrosion resistance is combined with the scale inhibitor HEDP, and is wrapped by LE to form the ZrO2 / HEDP composite material wrapped by slow-release lecithin with a scale inhibition function, and the ZrO2 / HEDP composite material can be subsequently applied to preparation of anti-corrosion and anti-scale coatings and has wide application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid silica gel materials, and in particular to a lecithin-wrapped ZrO2 / HEDP composite material and a preparation method thereof. Background Art

[0002] In the field of material technology, the research and development of composite materials has always been a hot topic, aiming to create new materials with new properties and functions by combining the excellent properties of different materials. ZrO2 (zirconium dioxide), as an inorganic non-metallic material, has a wide range of applications in many fields due to its excellent mechanical properties, corrosion resistance and good thermal stability. However, the use of ZrO2 alone is often difficult to meet the requirements of material versatility in certain specific applications.

[0003] HEDP (hydroxyethylidene diphosphonic acid) is a commonly used scale inhibitor with good chelating ability and dispersing properties. It can effectively prevent the scaling of calcium and magnesium ions in water and is widely used in water treatment, cooling system anti-scaling and other fields. By combining ZrO2 with HEDP, it is expected to obtain a composite material that has both the mechanical strength and corrosion resistance of ZrO2 and the scale inhibition function of HEDP.

[0004] However, how to effectively combine these two materials with very different properties and form a stable composite system is a technical problem. Simple physical mixing often fails to achieve the ideal dispersion effect and bonding strength, while chemical methods may introduce unnecessary impurities or change the original properties of the materials. Therefore, how to effectively combine ZrO2 and HEDP and further improve the performance and application range of the composite material is a major challenge in current research. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a lecithin-coated ZrO2 / HEDP composite material and a preparation method thereof.

[0006] In a first aspect, the present invention provides a method for preparing a lecithin-coated ZrO2 / HEDP composite material, the preparation method comprising the following steps:

[0007] Adding ZrO2 to an anhydrous ethanol solution containing hydroxyethylidene diphosphonic acid, followed by ultrasonic dispersion to obtain a first mixed solution;

[0008] Drying the first mixed solution until the solution is completely volatilized to obtain an intermediate;

[0009] The intermediate and an ethyl acetate solution containing lecithin are added to obtain a second mixed solution;

[0010] The second mixed solution is evaporated under reduced pressure until the solvent is completely volatilized to obtain the lecithin-coated ZrO2 / HEDP composite material.

[0011] Furthermore, the weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is (1.5-2.5):(0.3-0.8).

[0012] Furthermore, the weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is 2:0.5.

[0013] Furthermore, the weight percentage of hydroxyethylidene diphosphonic acid in the anhydrous ethanol solution is 3-8wt%.

[0014] Furthermore, the weight percentage of hydroxyethylidene diphosphonic acid in the anhydrous ethanol solution is 5wt%.

[0015] Furthermore, the working condition parameters of the drying include: a drying temperature of 55-65°C.

[0016] Furthermore, the weight ratio of the intermediate to the lecithin is (2-3):(0.3-0.8).

[0017] Furthermore, the weight ratio of the intermediate to the lecithin is 2.5:0.5.

[0018] Furthermore, the weight percentage of lecithin in the ethyl acetate solution is 0.3-0.8wt%, preferably 0.5wt%; the working condition parameters of the reduced pressure evaporation include: temperature of 45-55°C, preferably 50°C; pressure of -0.1Mpa, time of 1-2h, preferably 1h.

[0019] In a second aspect, the present invention provides a lecithin-encapsulated ZrO2 / HEDP composite material, wherein the lecithin-encapsulated ZrO2 / HEDP composite material is prepared by the preparation method of the lecithin-encapsulated ZrO2 / HEDP composite material described in any one of the first aspects.

[0020] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0021] The embodiment of the present invention provides a lecithin-encapsulated ZrO2 / HEDP composite material and a preparation method thereof. The method comprises the steps of adding ZrO2 to an anhydrous ethanol solution containing HEDP, performing ultrasonic dispersion, obtaining a uniform first mixed solution; then drying to obtain an intermediate; then mixing the intermediate with an ethyl acetate solution containing lecithin to obtain a second mixed solution; and finally removing the solvent by reduced pressure evaporation to obtain a lecithin-encapsulated ZrO2 / HEDP composite material. This composite material not only combines the excellent properties of ZrO2 and HEDP, but also forms a slow-release system with anti-scaling function through the encapsulation effect of LE, providing a new material selection for the subsequent preparation of anti-corrosion and anti-scaling coatings, etc., and has a wide range of uses and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0024] Figure 1 This is a scanning electron microscope image of HEDP / ZrO2 in the present invention.

[0025] Figure 2 This is a scanning electron microscope image of the lecithin-encapsulated ZrO2 / HEDP composite material of the present invention.

[0026] Figure 3 It is the infrared spectra of Lecithin, ZrO2 / HEDP / lecithin and ZrO2 / HEDP samples in the present invention.

[0027] Figure 4 It is the test result of the thermogravimetric analyzer in the present invention.

[0028] Figure 5 The wettability test results of the coating in the present invention are shown in FIG.

[0029] Figure 6 It is the test result of the adhesion performance of the coating in the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0032] In a first aspect, the present invention provides a method for preparing a lecithin-coated ZrO2 / HEDP composite material, the preparation method comprising the following steps:

[0033] Adding ZrO2 to an anhydrous ethanol solution containing hydroxyethylidene diphosphonic acid, followed by ultrasonic dispersion to obtain a first mixed solution;

[0034] Drying the first mixed solution until the solution is completely volatilized to obtain an intermediate;

[0035] The intermediate and an ethyl acetate solution containing lecithin are added to obtain a second mixed solution;

[0036] The second mixed solution is evaporated under reduced pressure until the solvent is completely volatilized to obtain the lecithin-coated ZrO2 / HEDP composite material.

[0037] The embodiment of the present invention provides a method for preparing a lecithin-encapsulated ZrO2 / HEDP composite material, wherein ZrO2 is added to an anhydrous ethanol solution containing HEDP, and ultrasonic dispersion is performed to obtain a uniform first mixed solution; then drying is performed to obtain an intermediate; the intermediate is then mixed with an ethyl acetate solution containing lecithin to obtain a second mixed solution; and finally the solvent is removed by reduced pressure evaporation to obtain a lecithin-encapsulated ZrO2 / HEDP composite material. This composite material not only combines the excellent properties of ZrO2 and HEDP, but also forms a slow-release system with a scale-inhibiting function through the encapsulation effect of LE, providing a new material selection for the subsequent preparation of anti-corrosion and anti-scaling coatings, etc., and has a wide range of uses and application prospects.

[0038] In the present invention, lecithin is abbreviated as "LE", and "HEDP" means hydroxyethylidene diphosphonic acid.

[0039] In some specific embodiments, the weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is (1.5-2.5):(0.3-0.8).

[0040] In some specific embodiments, the weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is 2:0.5.

[0041] In some specific embodiments, the weight percentage of hydroxyethylidene diphosphonic acid in the anhydrous ethanol solution is 3-8 wt %.

[0042] In some specific embodiments, the weight percentage of hydroxyethylidene diphosphonic acid in the anhydrous ethanol solution is 5 wt %.

[0043] In some specific embodiments, the drying working condition parameters include: a drying temperature of 55-65°C.

[0044] In some specific embodiments, the weight ratio of the intermediate to the lecithin is (2-3):(0.3-0.8).

[0045] In some specific embodiments, the weight ratio of the intermediate to the lecithin is 2.5:0.5.

[0046] In some specific embodiments, the weight percentage of lecithin in the ethyl acetate solution is 0.3-0.8wt%, preferably 0.5wt%; the working condition parameters of the reduced pressure evaporation include: temperature of 45-55°C, preferably 50°C; pressure of -0.1Mpa, time of 1-2h, preferably 1h.

[0047] In some specific embodiments, the preparation method of the lecithin-coated ZrO2 / HEDP composite material comprises the following steps:

[0048] First, weigh ZrO2, with a mass of 2 g, add it to 10 g of anhydrous ethanol solution containing 5 wt% HEDP, and then ultrasonically disperse it for about 10 minutes to form a uniform solution. Then, place the solution in a vacuum drying oven at 60°C and store it until it is dry, and the solution is completely volatilized to obtain an intermediate. Then, mix the intermediate with a mass of 2.5 g with 100 g of ethyl acetate solution containing 0.5 wt% lecithin and transfer it to a round-bottom flask, and rotary evaporate it at 50°C and -0.1 MPa pressure for 1 hour to completely volatilize the organic solvent to obtain the lecithin-wrapped ZrO2 / HEDP composite material.

[0049] In the second aspect, based on the same inventive concept, the present invention provides a lecithin-encapsulated ZrO2 / HEDP composite material, wherein the lecithin-encapsulated ZrO2 / HEDP composite material is prepared by the preparation method of the lecithin-encapsulated ZrO2 / HEDP composite material described in any one of the first aspects.

[0050] It should be noted that the raw material components involved in the lecithin-encapsulated ZrO2 / HEDP composite material and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or described, can be directly purchased from the market or can be prepared in-house according to existing preparation methods; at the same time, the operating steps involved in the preparation method, unless otherwise specified or described, can be carried out according to existing processes.

[0051] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0052] Example 1

[0053] This example provides a lecithin-encapsulated ZrO2 / HEDP composite material. The preparation method of the lecithin-encapsulated ZrO2 / HEDP composite material comprises the following steps:

[0054] First, weigh 2 g of ZrO2, add it to 10 g of anhydrous ethanol solution containing 5 wt% HEDP, and then ultrasonically disperse it for about 10 minutes to form a uniform solution. Then, place the solution in a vacuum drying oven at 60°C until it is dry, and the solution is completely evaporated to obtain an intermediate. Then, mix 2.5 g of the intermediate with 100 g of ethyl acetate solution containing 0.5 wt% lecithin and transfer it to a round-bottom flask, and rotary evaporate it at 50°C and -0.1 MPa pressure for 1 hour to completely evaporate the organic solvent to obtain a filler.

[0055] Example 2

[0056] This example provides a lecithin-encapsulated ZrO2 / HEDP composite material and a preparation method thereof, which is different from Example 1 only in that the weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is 1.5:0.3, and the weight ratio of the intermediate to the lecithin is 2:0.3.

[0057] Example 3

[0058] This example provides a lecithin-encapsulated ZrO2 / HEDP composite material and a preparation method thereof, which is different from Example 1 only in that the weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is 2.5:0.8, and the weight ratio of the intermediate to the lecithin is 3:0.8.

[0059] Test Case

[0060] In this example, the lecithin-wrapped ZrO2 / HEDP composite material obtained in Example 1 was used as a filler and applied to a commercially available PTFE (polytetrafluoroethylene) coating (product model Dongyue DF-331Z) to examine its performance.

[0061] 1) The coating preparation specifically includes the following process: 1) 10g PTFE solution is mixed and dispersed evenly with 0.5g filler to form a modified PTFE coating. 2) The commercially available PTFE (polytetrafluoroethylene) coating is dispersed evenly and sprayed with a spray gun at a high temperature of 60°C, the spraying pressure is 0.5±0.05MPa, the spraying height is 15±0.5cm, and the pure coating is marked as PTFE; the modified coating in 1) is sprayed onto the surface of the PE substrate using the same method, and is marked as a modified PTFE coating; finally, the sprayed coating is heated at 60°C for 12h to form a cured coating, and the coating thickness is 60±3μm.

[0062] 2) The preparation of QCMD chip sensor includes the following process: The QCMD chip sensor model is AC5AP14, and pure PTFE coating and modified PTFE coating are sprayed on the chip surface by the same spraying method as the coating preparation. The prepared two chip coating surfaces are exposed to 0.1mol / L NaOH solution for 28 days at 24°C and 50% humidity for alkaline corrosion, and are recorded as modified PTFE after corrosion (i.e., QCMD chip sensor containing modified PTFE coating) and PTFE after corrosion (i.e., QCMD chip sensor containing pure PTFE coating).

[0063] 3) The morphology and element distribution of calcium carbonate on the filler particles (i.e., lecithin-encapsulated ZrO2 / HEDP composite material) and the coating surface were analyzed by scanning electron microscopy, the surface properties of the filler were characterized by Fourier transform infrared spectroscopy, the encapsulation of ZrO2 / HEDP by lecithin was confirmed by thermogravimetric analyzer, the anti-scaling performance of the modified PTFE coating was tested by dissipative quartz crystal microbalance, the coating thickness was tested by ultrasonic coating thickness gauge, the sustained release performance and durability of the modified coating were tested by immersion method, the corrosion resistance was tested by electrochemical workstation (CHI760F), and the adsorption strength of the coating was tested by a hundred-grid knife in an environment of temperature of 24°C and relative humidity of 50% in accordance with ISO2409-1992 standard.

[0064] The test results are as follows:

[0065] Compared with lecithin-encapsulated HEDP / ZrO2 ( Figure 2 ), Figure 1The HEDP / ZrO2 filler in the spherical ZrO2 particle has a significantly smaller diameter, is granular, and is loosely distributed. It is composed of two different material structures, with HEDP particles dotted on the surface of the spherical ZrO2 particles. Figure 2 As shown in the figure, after lecithin encapsulates HEDP / ZrO2, the particle volume becomes larger and accumulates in the form of irregular bubbles, with obvious lecithin membrane structure. From the surface of the lecithin membrane, it can be seen that the HEDP / ZrO2 structure encapsulated inside is granular and protruding, which confirms the successful encapsulation of HEDP / ZrO2 by lecithin from the structure. Through the elemental analysis of the sample, it can be seen that the uniform distribution of the prepared HEDP / ZrO2 is a prerequisite for the successful encapsulation of the two substances by LE. After lecithin encapsulation, the internal elements of the lecithin membrane structure have the characteristics of HEDP and ZrO2 respectively, which confirms the successful encapsulation of HEDP / ZrO2 by LE from the elemental analysis.

[0066] The infrared spectra of Lecithin (i.e. pure lecithin), ZrO2 / HEDP / lecithin (i.e. lecithin encapsulated ZrO2 / HEDP composite material), and ZrO2 / HEDP samples are shown in the figure. Figure 3 b, bands 1710, 2910 and 2950-3050cm -1 They belong to the stretching vibration of C=O, the stretching vibration of -CH2- and the asymmetric bending vibration of -C=CH in the -CO-O- group. Figure 3 These three peaks can be observed in a and c, but Figure 3 Not observable in b. Figure 3 920-1120 and 1430-1490cm shown in c -1 The strong broad absorption peaks at and are attributed to the asymmetric bending vibrations of the P-(OH)2 and -CH3 bonds in HEDP, respectively. These two groups of peaks can be observed in Figures b and c, but in Figure 3 It cannot be observed in a. FTIR confirmed the assembly of ZrO2 / HEDP / lecithin.

[0067] The thermal stability of each component and its compound was tested by thermogravimetric analyzer. Figure 4 As shown in Figure 1, the decomposition temperature of HEDP is 169.6℃~343.7℃ (interval Ⅰ). Figure 4 As shown, the decomposition temperature of lecithin is 230.5~490.1℃ (interval II). Compared with pure lecithin, the intermediate of lecithin / ZrO2 has a slope peak at 449.8℃, where the slope peak at 449.8℃ corresponds to Figure 4 The slope peak of 387.9℃ is due to the fact that lecithin is wrapped on the surface of ZrO2 in a membrane state, which changes the heating area and thus changes the decomposition temperature range. In addition, compared with pure lecithin, Figure 4A new decomposition temperature range of 512.5-555.1℃ affected by ZrO2 was added, and there is a slope peak at 535.8℃, which corresponds to Figure 4 The decomposition temperature range is 493.2~573.7℃ (range Ⅲ), and the slope peak is 517.5℃. From the above analysis, it can be seen that HEDP mainly decomposes in temperature range I, and lecithin mainly decomposes in temperature range Ⅱ, which confirms the successful encapsulation of lecithin on HEDP / ZrO2 from the perspective of thermal stability.

[0068] 4) Wettability test analysis of the coating: The inner wall coating of the drainage pipe will be in contact with groundwater in actual use. Groundwater may penetrate the tiny holes, cracks and defects on the surface of the coating and reach the drainage pipe wall substrate, causing corrosion and scaling. Therefore, the coating needs to be hydrophobic. The conventional contact angle of polytetrafluoroethylene varies in the range of 90-108°, which is a hydrophobic material. This experiment tested the contact angle of the PTFE coating before and after the slow-release filler was added, and tested the contact angle change of the PTFE coating after 28 days of alkaline corrosion with 1 mol / L sodium hydroxide solution at 24°C and 50% humidity. Figure 5 As shown. It can be seen that the initial contact angle of the PTFE coating is 107.8°, which decreases to 96.5° after alkaline corrosion. The initial contact angle of the PTFE coating with slow-release filler is 109.1°, which slightly decreases to 107.8° after alkaline corrosion. Compared with pure PTFE coating, the incorporation of slow-release filler forms a rough structure on the coating surface, thereby increasing the initial contact angle. Although PTFE is chemically inert, alkaline corrosion can cause structural changes and aging on the PTFE surface. At the same time, the adhesion between the PTFE coating and the PE substrate is weakened, resulting in the destruction of the integrity of the coating, thereby reducing the hydrophobicity. The incorporation of ZrO2 in the filler can effectively improve the strength and hardness of the PTFE coating, and effectively improve the alkali resistance of the coating. Lecithin can reduce the surface tension of the PTFE coating, so that the coating can better combine with the PE surface and enhance the adhesion of the coating on the PE surface. Therefore, the PTFE coating with slow-release filler has a small change in contact angle after alkaline corrosion, which can make the PTFE coating maintain hydrophobicity for a long time in an alkaline environment.

[0069] 5) Coating adhesion test: The coating adhesion was tested using the hundred-grid knife method, with the blade cutting speed at 30 mm / s. The results are as follows: Figure 6 As shown, from Figure 6 It can be seen that the coating has good adhesion and there is no peeling at the edges and intersections of the scribed lines. The pure PTFE coating has peeling, with an area of ​​about xx%. The reason is that the choline and glycerophosphate in LE increase the adhesion of PTFE on the PE substrate, making the coating denser.

[0070] 6) Analysis of anti-fouling performance of coating based on QCM-D: Quartz crystal microbalance dissipation (QCMD) can non-invasively monitor the interface between the sensor and the surrounding medium, and describe in detail the interface mass deposition, conformational evolution, solvation and viscoelasticity. This method is widely used in the study of nanoparticle deposition, vesicle fusion, interface binding and adsorption, phase change and reaction kinetics. The test results show that before alkaline corrosion, the frequency change value of modified PTFE finally stabilized at about -45.89Hz, the adsorption mass was about 344.91ng / cm2, and the frequency change value of pure PTFE was stable at about -63.41Hz, the adsorption mass was about 476.58ng / cm2, and the anti-fouling performance of modified PTFE was improved by about 38.18% compared with pure PTFE. After alkaline corrosion, the frequency change value of modified PTFE stabilized at about -48.49Hz, the adsorption mass was about 364.45ng / cm2, and the anti-fouling ability decreased by 5.67% compared with that before alkaline corrosion. After alkaline corrosion, the frequency of pure PTFE continued to change in three stages. By 13 hours, the frequency change value reached -85.25Hz. Compared with before corrosion, the anti-scaling ability decreased by about 34.44%, and compared with modified PTFE, the anti-scaling ability was about 75.81%. It can be seen that the addition of fillers can not only improve the anti-scaling ability, but also continue to maintain excellent anti-scaling performance after alkaline corrosion. The PTFE coating itself has a strong resistance to alkaline corrosion. However, after alkaline corrosion, the anti-scaling performance of the pure PTFE coating is greatly reduced. This may be because the long-term alkaline environment will cause the coating to fall off or peel off from the substrate, thereby destroying the integrity of the coating and causing the coating to lose anti-scaling performance. The addition of fillers greatly improves the adhesion and self-strength between the PTFE coating and the PE substrate, which can ensure the integrity of the coating for a long time, so that the modified PTFE can also play a long-term anti-scaling performance in an alkaline corrosion environment.

[0071] 7) Anti-scaling mechanism of coating: Based on the above test results, the modified PTFE coating exhibits excellent slow-release performance, corrosion resistance, adhesion and anti-scaling performance. The main reasons are as follows. When the lecithin-wrapped slow-release PTFE coating is applied to the inner wall of the PE pipe, the HEDP in the surface filler is slowly released after the coating contacts the groundwater. 2+ 、CO3 2-HEDP forms a complex with calcium ions in water to prevent the precipitation of calcium carbonate. In addition, PTFE itself is hydrophobic and has a certain anti-scaling ability from a physical point of view. The addition of slow-release fillers increases the roughness of the coating surface, thereby improving the hydrophobicity of the coating and further improving the physical anti-scaling performance. ZrO2 added to the filler can play a role in reinforcing the aggregate. The strong alkali resistance of ZrO2 can reduce the alkaline corrosion of the coating during long-term service and greatly improve the durability of the coating. Due to the hydrophobicity and low surface energy of PTFE itself, its adhesion on the PE surface is poor. As a surfactant, the addition of lecithin can reduce the surface tension of the PTFE coating and improve the adhesion through interaction with the PE surface, so that PTFE can better bond with the PE surface.

[0072] In summary, the embodiments of the present invention provide a lecithin-coated ZrO2 / HEDP composite material and a preparation method thereof, and a long-term anti-corrosion and anti-scaling coating sample is prepared after adding PTFE. The coating can maintain high durability, alkali resistance and long-term anti-scaling performance in an alkaline environment. Since lecithin can improve the adhesion between PTFE and the PE substrate, in the Baige experiment, the adhesion of the modified coating can meet the international standard, indicating that the modified coating can be stably adsorbed on the PE substrate. The sustained-release property of lecithin allows the coating to slowly release the HEDP scale inhibitor after contacting groundwater. With the long-term scouring of groundwater, the scale inhibitor inside the coating is also released, which greatly improves the long-term anti-scaling performance of the coating from the perspective of chemical anti-scaling. The addition of ZrO2 in the filler slightly improves the surface roughness of the coating, enhances the hydrophobicity of the PTFE coating, and improves the physical anti-scaling performance of the coating. The high hardness and high strength of ZrO2 can improve the strength of the PTFE coating. At the same time, the strong alkali resistance of ZrO2 enables the coating to remain intact in a long-term alkaline corrosion environment and exert long-term anti-scaling ability. The QCMD test results show that the modified coating with slow-release fillers has excellent alkaline corrosion resistance and anti-scaling ability. The development of this new material provides a new idea for long-term anti-scaling in the field of tunnel engineering materials and has broad application prospects.

[0073] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0074] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a lecithin-coated ZrO2 / HEDP composite material, characterized in that: The preparation method comprises the following steps: Adding ZrO2 to an anhydrous ethanol solution containing hydroxyethylidene diphosphonic acid, followed by ultrasonic dispersion to obtain a first mixed solution; Drying the first mixed solution until the solution is completely volatilized to obtain an intermediate; The intermediate and an ethyl acetate solution containing lecithin are added to obtain a second mixed solution; The second mixed solution is evaporated under reduced pressure until the solvent is completely volatilized to obtain the lecithin-coated ZrO2 / HEDP composite material.

2. The method for preparing the lecithin-encapsulated ZrO2 / HEDP composite material according to claim 1, characterized in that: The weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is (1.5-2.5):(0.3-0.8).

3. The method for preparing the lecithin-encapsulated ZrO2 / HEDP composite material according to claim 1, characterized in that: The weight ratio of the ZrO2 to the hydroxyethylidene diphosphonic acid is 2:0.

5.

4. The method for preparing the lecithin-encapsulated ZrO2 / HEDP composite material according to claim 1, characterized in that: The weight percentage of hydroxyethylidene diphosphonic acid in the anhydrous ethanol solution is 3-8wt%.

5. The method for preparing the lecithin-encapsulated ZrO2 / HEDP composite material according to claim 1, characterized in that: The weight percentage of hydroxyethylidene diphosphonic acid in the anhydrous ethanol solution is 5 wt %.

6. The method for preparing the lecithin-coated ZrO2 / HEDP composite material according to claim 1, characterized in that: The working condition parameters of the drying include: a drying temperature of 55-65°C.

7. The method for preparing the lecithin-coated ZrO2 / HEDP composite material according to claim 1, characterized in that: The weight ratio of the intermediate to the lecithin is (2-3):(0.3-0.8).

8. The method for preparing the lecithin-coated ZrO2 / HEDP composite material according to claim 1, characterized in that: The weight ratio of the intermediate to the lecithin is 2.5:0.

5.

9. The method for preparing the lecithin-coated ZrO2 / HEDP composite material according to claim 1, characterized in that: The weight percentage of lecithin in the ethyl acetate solution is 0.3-0.8wt%; the working condition parameters of the reduced pressure evaporation include: temperature of 45-55°C, pressure of -0.1Mpa, and time of 1-2h.

10. A lecithin-coated ZrO2 / HEDP composite material, characterized in that: The lecithin-coated ZrO2 / HEDP composite material is prepared by the preparation method of the lecithin-coated ZrO2 / HEDP composite material according to any one of claims 1 to 9.